2016
DOI: 10.1371/currents.outbreaks.711379ace737b7c04c89765342a9a8c9
|View full text |Cite
|
Sign up to set email alerts
|

FLIRT-ing with Zika: A Web Application to Predict the Movement of Infected Travelers Validated Against the Current Zika Virus Epidemic

Abstract: Introduction: Beginning in 2015, Zika virus rapidly spread throughout the Americas and has been linked to neurological and autoimmune diseases in adults and babies. Developing accurate tools to anticipate Zika spread is one of the first steps to mitigate further spread of the disease. When combined, air traffic data and network simulations can be used to create tools to predict where infectious disease may spread to and aid in the prevention of infectious diseases. Specific goals were to: 1) predict where trav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…A recent published paper on Zika epidemics have shown that the public showed more concern about the complications or consequences it had for women and babies, whereas WHO and CDC increased Zika epidemics guidelines and precautionary measures for women at child bearing information, awareness and active education. Whereas, another study showed such approach that tends to be episodic and ephemeral rather than coherent, comprehensive and sustained by all stakeholders over time [19,20]. Public authority announcements can give the importance of trust and credibility for information acceptance using Google Trends.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent published paper on Zika epidemics have shown that the public showed more concern about the complications or consequences it had for women and babies, whereas WHO and CDC increased Zika epidemics guidelines and precautionary measures for women at child bearing information, awareness and active education. Whereas, another study showed such approach that tends to be episodic and ephemeral rather than coherent, comprehensive and sustained by all stakeholders over time [19,20]. Public authority announcements can give the importance of trust and credibility for information acceptance using Google Trends.…”
Section: Introductionmentioning
confidence: 99%
“…Keeping the existing community and public informed about updates and mitigation wider reach through SMS and internet-based applications, social media engagement and participation individuals from remote rural communities. Moreover, to sharing objective and true journalism on burial practices on Ebola spread, monitoring closed circuit and other mass media surveillance data and information access and uptake against Zika and Ebola epidemics in high-and low risk zones and cross-borders entries ports, patients, individuals and collective displacement tracing, tracking and monitoring [9,14,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations